1997
DOI: 10.1017/s0014479797003062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foliar Application of Glycinebetaine on Yield Components of Drought-Stressed Tobacco Plants

Abstract: Two glasshouse experiments were conducted at the Department of Plant Production, University of Helsinki, Finland, to study the eect of foliar application of aqueous 0.1 and 0.3M glycinebetaine on leaf growth of drought-stressed tobacco (Nicotiana tabacum L.) cv. Samsun. Leaf nitrogen and glycinebetaine concentrations were estimated periodically. After 16 days of treatment, leaves were harvested, and fresh and dry weights, and area determined. The number of total and green leaves was also recorded. Signi®cant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 9 publications
2
24
0
Order By: Relevance
“…In contrast, Naidu, et al (1998) reported a highly significant role of supplied GB in increasing the yield of cotton. However, the positive effects of foliar spray of GB 100-achene weight of sunflower lines grown under water limited environment as observed in the present study has also been however also reported in different crops such as tomato (Makela, et al, 1998), tobacco (Agboma, et al, 1997b), maize (Agboma, et al, 1997a), cotton (Gorham, et al, 2000) and wheat (Diaz-Zarita, et al, 2001). There are however, some contrasting reports indicating no effect of supplied GB on yield of wheat (Agboma, et al, 1997a) and cotton (Meek, et al, 2003).…”
Section: Discussionsupporting
confidence: 76%
“…In contrast, Naidu, et al (1998) reported a highly significant role of supplied GB in increasing the yield of cotton. However, the positive effects of foliar spray of GB 100-achene weight of sunflower lines grown under water limited environment as observed in the present study has also been however also reported in different crops such as tomato (Makela, et al, 1998), tobacco (Agboma, et al, 1997b), maize (Agboma, et al, 1997a), cotton (Gorham, et al, 2000) and wheat (Diaz-Zarita, et al, 2001). There are however, some contrasting reports indicating no effect of supplied GB on yield of wheat (Agboma, et al, 1997a) and cotton (Meek, et al, 2003).…”
Section: Discussionsupporting
confidence: 76%
“…All the higher plants do not have the capacity to accumulate GB [39]. Evidence reveals that soybean is normally a low-accumulator of GB [43], with an average content less than 5 μmol/g dry weights [44]. Foliar application of GB could increase its content in soybean plant up to 60 μmol/g dry weights, leading to an improvement in photosynthesis activity, nitrogen fixation, leaf area development, and seed yield of both well irrigated and drought-stressed soybean plants [45, 46].…”
Section: Exogeneous Application Of Gb In Plants Enhancing Abiotic Stressmentioning
confidence: 99%
“…It is well established that its exogenous application might have some advantages as it improves drought tolerance in plants (Agboma et al 1997;Gorham et al 2000;Iqbal et al 2008;Mahmood et al 2009). It has been also reported earlier that rate and timing of GB application significantly affects drought tolerance ability of sunflower (Iqbal et al 2008(Iqbal et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It has been also reported earlier that rate and timing of GB application significantly affects drought tolerance ability of sunflower (Iqbal et al 2008(Iqbal et al , 2009). This shot-gun approach of exogenous application of GB has been used to increase the drought tolerance in some other crop species (Agboma et al 1997;Makela et al 1998;Gorham et al 2000).…”
Section: Introductionmentioning
confidence: 99%